Iatrogenic bladder rupture following repeated cystocentesis - Matos, M. G.; Viana, D. A.; Lopes, C. E. B.; Pimentel, S. P.; Rodrigues, F. R. N. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2018)
Cystocentesis is a medical procedure to collect urine for diagnostic evaluation and also temporarily decompress the urinary bladder in animals with urethral obstruction. When performed correctly is a safe procedure, as long as it is performed by trained personnel. Otherwise there is risk of rupture of the bladder leading to uroabdomen and hemorrhage, culminating in some cases with patient’s death. Medical procedures are a major reason to perform forensic autopsy, as some of these can cause iatrogenic conditions, which represent a state of illness, adverse effects or complications caused by or resulting from medical intervention, sometimes considered as an error.